Comparative study of the effectiveness of treatments for androgenetic alopecia through the capillary intradermotherapy technique: minoxidil and finasteride (Research, Society and Development, 2021)
Objective: to compare relevant results regarding the effectiveness of the use of Minoxidil, growth factors and some vitamins with the association Finasteride, growth factors and vitamins by the capillary intradermotherapy technique for the treatment of Androgenetic Alopecia. Methods: The research was carried out in a private clinic in the city of Patos-PB. Ten patients with Androgenetic Alopecia were evaluated, divided into two groups of five people each, according to similar characteristics. Group A received capillary intradermotherapy with Minoxidil, growth factors and vitamins, while Group B received Finasteride, growth factors and vitamins. The criteria used for comparison were evaluated by the medical evolution questionnaire, taking into account the increase or decrease in capillary volume and the decrease in alopecia. After that, the data were systematized and compared with the updated literature on the proposed theme. Results: A slight superiority related to the increase in capillary volume of patients in group A was illustrated. With regard to capillary drop, the results remained practically similar between patients in both groups. Conclusion: There is a need for studies with a larger sample size, aiming at a more reliable result in search of a more significant clinical effect for this disease.